1999
DOI: 10.1523/jneurosci.19-10-04132.1999
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Mediates Circadian Rhythms of Rod–Cone Dominance in the Japanese Quail Retina

Abstract: A circadian clock modulates the functional organization of the Japanese quail retina. Under conditions of constant darkness, rods dominate electroretinogram (ERG) b-wave responses at night, and cones dominate them during the day, yielding a circadian rhythm in retinal sensitivity and rod-cone dominance. The activity of tyrosine hydroxylase, the rate-limiting enzyme in dopamine synthesis, also exhibits a circadian rhythm in the retina with approximately threefold higher levels during the day than at night. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 62 publications
4
84
1
2
Order By: Relevance
“…A rhythm in ERG sensitivity to light was also demonstrated, but the extent of threshold variation was only ϳl.0 log unit, suggesting that regulation of visual sensitivity by the circadian clock mechanism occurs at several different levels in the visual system (Li and Dowling, 1998). Several studies have suggested that dopamine is a circadian clock modulator in the retina (Besharse and Iuvone, 1983;Kolbinger et al, 1990;McCormack and Burnside, 1992;Manglapus et al, 1999). We measured behaviorally as well as by ERG the visual sensitivity of DA-IPC-depleted animals as a function of time of day.…”
Section: Dopamine and Retinal Circadian Rhythmicitymentioning
confidence: 92%
“…A rhythm in ERG sensitivity to light was also demonstrated, but the extent of threshold variation was only ϳl.0 log unit, suggesting that regulation of visual sensitivity by the circadian clock mechanism occurs at several different levels in the visual system (Li and Dowling, 1998). Several studies have suggested that dopamine is a circadian clock modulator in the retina (Besharse and Iuvone, 1983;Kolbinger et al, 1990;McCormack and Burnside, 1992;Manglapus et al, 1999). We measured behaviorally as well as by ERG the visual sensitivity of DA-IPC-depleted animals as a function of time of day.…”
Section: Dopamine and Retinal Circadian Rhythmicitymentioning
confidence: 92%
“…GAP-43 is present in tyrosine hydroxylase-positive retinal amacrine cells, suggesting that the protein may be involved in the release of dopamine from the terminals of these cells located in the inner plexiform layer [46]. The release of dopamine in the retina has been implicated in light/dark adaptation [58]. The levels of released dopamine increase in almost all retinae with light adaptation, and dopamine mimics the effects of light in many instances [98].…”
Section: Gap-43 In the Adult Retina And Corneamentioning
confidence: 99%
“…For example, dopamine-mediated suppression of rod output might involve other actions of D 2 /D 4 dopamine receptor activation in photoreceptors, such as inhibition of Na + /K + -ATPase activity (Shulman & Fox, 1996), increased rod/cone coupling , Manglapus et al, 1999, and inhibition of I h in rods (Akopian & Witkovsky, 1996). There may also be contributions from other neuromodulators known to influence rod function, such as nitric oxide, somatostatin, or adenosine (Kurenny et al, 1994;Akopian et al, 2000;Stella et al, 2002).…”
Section: Introductionmentioning
confidence: 99%